The Business of Placing Canadian Children and Youth “At-Risk” - Wotherspoon, Terry; Schissel, Bernard (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
This article examines discourses and practices associated with designating some children and youth as being “at-risk” of academic and social failure in and out of school. To respond effectively to “at-risk” learners requires a refocusing of policy and research, an informed political and administrative will, effective use of sufficient resources, and systematic co- ordination of existing knowledge bases. We explore effective strategies based on a social justice vision of schooling and child development, arguing for an integrated understanding of and approach to child and youth-related activities and initiatives across school, community, socio-structural, and public policy spheres. L’article traite des discours et des pratiques associés au fait de désigner certains enfants et jeunes comme des personnes « à risque » à l’école et dans la société. Si l’on veut répondre aux besoins des apprenants « à risque », il faut une réorientation des politiques et des recherches, une volonté politique éclairée, des ressources suffisantes judicieusement utilisées et une coordination systématique des bases de connaissances existantes. Les auteurs explorent des stratégies efficaces fondées sur une vision de l’éducation et du développement de l’enfant axée sur la justice sociale. Ils prônent une approche intégrée des activités et des initiatives à l’école, dans la collectivité, dans les sphères sociostructurelles et en matière de politiques publiques.